The Use of Facebook to Promote the Learning of Spanish as a Foreign Language Outside the Classroom (International Journal of Language, Literacy and Translation, 2025)
As the age old adage goes, ‘practice makes perfect’ and this is especially true for language learners. In order to polish language skills, students are advised to practice the language outside of the dedicated class time. For students learning Spanish as a foreign language in Malaysia, this can be a challenge due to several factors such as having no one to speak to, the fear of making mistakes, and the fear of embarrassment. This paper looks at the use of a Facebook group as a platform for students to practice Spanish outside the designated classroom time. The study was conducted on a group of 12 undergraduates enrolled in a beginner-level Spanish language university elective course, who were given the daily task to publish posts in Spanish according to a list of given topics during a five-week period. The effectiveness of the task and the Facebook group was assessed by a questionnaire answered by the students at the end of that duration. Findings reveal that using Facebook provided more opportunities for students to practise Spanish and aided in the retention and recall of the language.